Monetary and fiscal policy in monetary union under the zero lower bound constraint - Stefanie Flotho (University of Freiburg, Department of International Economic Policy (iep), 2012)
This paper explicitly models strategic interaction between two independent national fiscal authorities and a single central bank in a simple New Keynesian model of a monetary union. Monetary policy is constrained by the zero lower bound on nominal interest rates. Coordination of fiscal policies does not always lead to the best welfare effects. It depends on the nature of the shocks whether governments prefer to coordinate or not coordinate. The size of the government multipliers depend on the combination of the intraunion competitiveness parameters. They get larger in case of implementation lags of fiscal policy.
Keywords: E31; E52; E58; E61; E62; E63; F33; 330; Monetary Union; Fiscal Policy; Zero Lower Bound on nominal interest rates; zero interest rate policy; Non-coordination; Währungsunion; Finanzpolitik; Internationale Wirtschaftspolitik; Geldpolitik; Zinspolitik; Neukeynesianische Makroökonomik; Wohlfahrtsanalyse; Theorie